2006
DOI: 10.1364/oe.14.001582
|View full text |Cite
|
Sign up to set email alerts
|

Compact source of continuously and widely-tunable terahertz radiation.

Abstract: We report a THz radiation source based on the technique of non-collinear phasematched parametric generation. The source, which is compact and operable at room temperature, generates nanosecond pulses of peak power and energy greater than 1W and 5 nJ respectively. The radiation is continuously tunable over the range 1.2-3.05 THz and is of narrow spectral bandwidth (<100 GHz). The use of intersecting pump and parametric wave cavities results in threshold pump pulse energies below 1 mJ (from a Nd:YAG laser excite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(44 citation statements)
references
References 10 publications
0
43
0
1
Order By: Relevance
“…We have validated this at a number of spot frequencies and shows that practical high-performance QOFRs in quasi-optical isolators are feasible to frequencies of 500 GHz and beyond, where no alternatives exist. Indeed, recent measurements using a newly developed terahertz source [31] have shown that the Faraday effect still persists in hexaferrites at frequencies above 1 THz. Insertion loss becomes quite severe at these frequencies (more than 10 dB), but such devices may still be useful for some sub-millimeter spectroscopic applications, where measurement accuracy can be more limited by system standing waves than by other signal-to-noise considerations.…”
Section: Discussionmentioning
confidence: 99%
“…We have validated this at a number of spot frequencies and shows that practical high-performance QOFRs in quasi-optical isolators are feasible to frequencies of 500 GHz and beyond, where no alternatives exist. Indeed, recent measurements using a newly developed terahertz source [31] have shown that the Faraday effect still persists in hexaferrites at frequencies above 1 THz. Insertion loss becomes quite severe at these frequencies (more than 10 dB), but such devices may still be useful for some sub-millimeter spectroscopic applications, where measurement accuracy can be more limited by system standing waves than by other signal-to-noise considerations.…”
Section: Discussionmentioning
confidence: 99%
“…Typically the spectral width of the primary idler-wave, and hence the accompanying THz radiation, is ≈ 50GHz (FWHM). A fuller description of this device and its performance characteristics is given in [5].…”
Section: Experimental Devicementioning
confidence: 99%
“…Firstly the capability for angle tuning over a wide spectral range (0.5-4THz [5]) is retained; secondly the significant loss of the nonlinear coefficient resulting from quasi-phase matching is avoided and finally the use of separate cavities as opposed to one common cavity provides the flexibility required for individual cavity optimisation. It is therefore important that cascaded processes for further overcoming the Manley-Rowe limit continue to be explored in the context of THz devices based on the use of bulk lithium niobate combined with non-collinear phase matching geometries.…”
Section: Thresholds and Pulse Energies Of Pump And Idler Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now various optical and electrical methods have been used for THz sources [1][2][3][4][5][6][7][8][9][10][11]; however at present, achieving compact, efficient, and economic sources remains a challenge to scientists and engineers [11][12][13][14]. One of the main optical methods for CW THz wave generation is heterodyne method that uses THz beat frequency of two frequency-locked laser beams with two different frequencies [10,11].…”
Section: Introductionmentioning
confidence: 99%